Relationship between Tooth Brushing Behavior and Dental Caries in Children at 27 Sungai Sapih Public Elementary School Kuranji, Padang City - Sri P. Utami; Intan B. E. Mahata; Valendriyani Ningrum; Ricky Amran; Resi Wiyanti (e-GiGi, 2024)
Caries is often experienced in mid-childhood (10-12 years) which is referred to as a vulnerable period, because at that time milk teeth begin to fall out and first permanent teeth begin to erupt. Tooth brushing is the most recommended primary prevention in maintaining dental and oral health. This study aimed to evaluate the relationship between tooth brushing behavior and dental caries in children at 27 Sungai Sapih Kuranji Public Elementary School, Padang City. This was a quantitative study with an analytical and observational approach. Population were all students in grades 4 and 5, totaling 114 students obtained with total sampling technique. Data were analyzed using the Spearman test, and were processed using computerized program SPSS IBM version 25.0. The results showed that most subjects had moderate tooth brushing behavior (82.5%), and the highest percentage of dental caries level was very low (49.1%). The Spearman test showed a significant relationship between tooth brushing behavior and dental caries level among the subjects (p=0.001). In conclusion, there was a significant relationship between tooth brushing behavior and dental caries in children at SD Negeri 27 Sungai Sapih Kuranji, Padang City. It is recommended for dental health workers to educate the students about the importance of dental and oral care and how to do tooth brushing properly and correctly. Keywords: tooth brushing behavior; dental caries; elementary school children; dental and oral health